The modulation of oceanic moisture transport by the hemispheric annular modes - Nieto, Raquel; Castillo, Rodrigo; Drumond, Anita (Frontiers in Earth Science, 2014)
Leaving aside the contribution made by recycling, it is the main oceanic moisture sources that are responsible for most of the precipitation that falls on the continents. The transport of moisture from these sources can be affected by large-scale variability according to the hemispheric annular modes. The influence of the two dominant modes of extratropical winter climate: the Northern and the Southern Annular Modes (NAM and SAM) are herein investigated to assess how they affect the transport of moisture from the major oceanic moisture sources. A Lagrangian model was used, together with ERA-Interim reanalysis data (1979-2012), and differences between the composites of the six strongest higher and lower events observed for both phases of the two modes for the period were analysed. The method is able to reproduce the general pattern of known variations for both annular patterns. Lower values of the NAM Index are associated with the displacement of the storm track towards tropical latitudes. Thus, moisture transport is enhanced from the Northern Pacific towards the northeastern basin and from the Northern Atlantic and Mediterranean towards southern Europe. On the other hand, during higher values of NAM, moisture transport is favoured from the Northern Pacific towards eastern Asia, and moisture transport is enhanced from the Northern Atlantic towards the Caribbean Sea. In the Southern Hemisphere, during higher values of SAM more moisture is transported from the Atlantic and Indian oceanic sources southwards and eastwards than during the opposite phase. In this SAM phase it is also noted by an enhancement of moisture transport from the Coral Sea and Southern Pacific sources towards the Indian Ocean/West Pacific Warm Pool. Southeastern South America received more moisture from the Pacific and Atlantic sources during years with a lower SAM, episodes which also favoured the influx of moisture from the Southern Atlantic towards Africa, causing monsoon conditions to occur.